Palliative care for people living with HIV/AIDS in Uganda: investigation of patients and caregivers' outcome and professional perspectives - Too, Wesley (2011)
Background: Although antiretroviral treatment is expanding in sub-Saharan Africa, the World Health Organization advocates for integration of palliative care with HAAR T because pain, other distressing symptoms and complex psychosocial challenges persist throughout the HIV trajectory. Palliative care improves the outcome for patients with HIV and may complement antiretroviral treatment by increasing adherence through better management of side effects from the treatment, providing patient and family-centred holistic care, and giving end-of-life care when necessary. However, integrating what have become two disciplines is challenging.